Analyzing sentiment shifts in news coverage of occupational accidents: A case study of the Amasra mining disaster in Türkiye - Dikbiyik, Derya; Alp, Selcuk (SAGE PUBLICATIONS INC, 2026)
Background Workplace accidents, particularly those resulting in fatalities, are critical public health and labor issues with profound human and societal consequences. Beyond immediate impacts, such incidents often attract extensive media coverage, which can shape public perception and emotional responses. Understanding how emotions evolve in media narratives is essential for effective crisis communication and public engagement. The Amasra mining disaster in T & uuml;rkiye, which caused the death of 41 miners in 2022, provided a significant case to explore emotional dynamics in news reporting.Objective This study aimed to analyze how emotional tone and sentiment in print media shift over time in response to a major workplace accident. The goal was to develop and apply a novel sentiment analysis framework to evaluate public discourse during the accident, post-accident, and trial periods.Methods A lexicon-based sentiment analysis approach was used, incorporating word frequency analysis, expert classification of emotions, and Levenshtein distance to normalize word variations. News articles from ten major Turkish media outlets were collected and processed. Sentiment polarity (positive, neutral, negative) and Plutchik's eight-emotion model (e.g., sadness, anger, fear) were applied across three defined timeframes: the accident period (October 14-16, 2022), post-accident period (until December 13, 2024), and trial period (December 13-15, 2024).Results The analysis showed a decrease in neutral sentiment and a steady increase in negative sentiment over time. Emotionally, sadness was most prevalent immediately after the accident but declined in the following periods, while anger increased, especially during the trial. These results indicate a shift from grief to frustration and demands for accountability. Fear and surprise remained consistently present across all periods.Conclusions The study demonstrates that emotional dynamics in media coverage of workplace disasters evolve predictably, offering critical insights for media professionals, policymakers, and safety regulators. Monitoring such emotional shifts can enhance crisis communication strategies, improve public trust, and inform policy interventions. However, the study is limited by its reliance on a lexicon-based approach and the exclusion of social media data, which may have offered a broader perspective on public sentiment. To understand societal responses to occupational accidents through media narratives, the proposed sentiment analysis approach provides a valuable tool.
Keywords: sentiment analysis; data mining; emotios; media; occupational accident; amasra mining disaster; Public, Environmental & Occupational Health